2009
DOI: 10.4028/www.scientific.net/msf.610-613.1022
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nitride Surface Modification and Cell Adhesion

Abstract: Silicon microelectrode arrays (Si MEAs) have great potential in recording of neural activity; the biocompatibility of silicon nitride has gained much attention as a part of Si MEAs. In this study, we used alternating polycations, polyethyleneimine (PEI), and polyanions, gelatin, to fabricate multilayer films built up by LbL deposition on silicon nitride wafers. Then the samples surfaces were characterized by contact angle system and atomic force microscopy (AFM). The amount of proteins adsorbed on silicon nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Due to the contact angle and contact angle hysteresis, the behavior of water droplets on the tilted surface was different. 40 Weeks et al 22 had measured the meniscus morphology and found that when the meniscus was in equilibrium, the contact angle of the silicon nitride tip was close to zero, but while the contact angle of the silicon nitride surface was 61°, 41 the experimental data conflicted with the theoretical contact angle. It indicates that the contact angle gradually decreases during the growth of meniscus to adapt to the balance of surface energy.…”
Section: Changing Process Of Meniscus Between the Cone Tip And Graphe...mentioning
confidence: 99%
“…Due to the contact angle and contact angle hysteresis, the behavior of water droplets on the tilted surface was different. 40 Weeks et al 22 had measured the meniscus morphology and found that when the meniscus was in equilibrium, the contact angle of the silicon nitride tip was close to zero, but while the contact angle of the silicon nitride surface was 61°, 41 the experimental data conflicted with the theoretical contact angle. It indicates that the contact angle gradually decreases during the growth of meniscus to adapt to the balance of surface energy.…”
Section: Changing Process Of Meniscus Between the Cone Tip And Graphe...mentioning
confidence: 99%